A case of nasal septal perforation caused by bevacizumab for advanced cervical cancer. Issue 2 (9th December 2020) - Taira, Yusuke; Shimoji, Yuko; Nakasone, Tadaharu; Arakaki, Yoshihisa; Nakamoto, Tomoko; Kudaka, Wataru; Aoki, Yoichi
Abstract: Nasal septal perforation caused by bevacizumab is rarely reported in other cancers such as ovarian cancer and breast cancer, but it has not been reported in cervical cancer. A 48‐year‐old woman with a medical history of chronic allergic rhinitis was diagnosed stage 4B (T2bN1M0) cervical cancer and paclitaxel and carboplatin along with bevacizumab (triweekly) were administered. After eight courses of chemotherapy, nasal septal perforation was noted. The possibility of nasal septal perforation by bevacizumab was considered by excluding other causes. We report the first case of nasal septal perforation caused by bevacizumab for advanced cervical cancer.